(untitled) (Palimpsesto, 2020)
The relationship between conservative Latin American Christian political-religious networks and the interests of the United States over Latin America during the Cold War will be analyzed. To this end, three types of conservative religious movements with a wide diffusion during this period will be analyzed: The Protestant conservatism, Tradición Familia y Propiedad fundamentalist Catholic movement and the Opus Dei neo-fundamentalist movement. It will distinguish the favorable impact on American interests that it had, political abstentionism, conservative intra-ecclesial politics, the creation of confessional political parties and support for de facto governments through entering key positions in the state and supporting paramilitary groups.